THE POST-ACQUISITION PERFORMANCE OF ACQUIRED COMPANIES: EVIDENCE FROM THE REBULIC OF SERBIA - Savović, Slađana (Economic Annals, 2016)
This paper explores the post-acquisition performance of acquired companies in the Republic of Serbia, and whether company size is a factor of postacquisition performance. The data were collected from 91 managers in 10 acquired companies in Serbia. The acquiring companies came from Germany, Austria, Italy, Switzerland, Belgium, Norway, Greece, and Serbia. The results of the analysis show that 70% of managers believed that there had been improvement in post-acquisition performance. The improvement in performance was achieved for the most part by cost reduction. The results of this study indicate that there are statistically significant differences between large, medium, and small companies. Large companies had the best improvement in financial performance, and medium companies were the best regarding improvement of non-financial performance.